Sight lines - Sze, Arthur (Copper Canyon Press, 2019)
"From the current phenomenon of drawing calligraphy with water in public parks in China to Thomas Jefferson laying out dinosaur bones on the White House floor, from the last sighting of the axolotl to a man who stops building plutonium triggers, Sight Lines moves through space and time and brings the disparate and divergent into stunning and meaningful focus. In this new work, Arthur Sze employs a wide range of voices--from lichen on a ceiling to a man behind on his rent--and his mythic imagination continually evokes how humans are endangering the planet; yet, balancing rigor with passion, he seizes the significant and luminous and transforms these moments into riveting and enduring poetry
Keywords: American poetry -- 21st century.; LITERARY CRITICISM -- Poetry.; American poetry; 2000-2099